Not another task force - The, Edge (The Edge, 2017)
Last week, Universiti Utara Malaysia Political and International Studies senior lecturer, Md Shukri Shuib, said the government should establish a special information task force to counter the negative perception of Umno and Barisan National leaders being spread by the opposition.